PENAMBAHAN KINESIOTAPING PADA INTERVENSI ABDOMINAL STRETCHING EXERCISE LEBIH BAIK DIBANDINGKAN DENGAN INTERVENSI ABDOMINAL STRETCHING EXERCISE TERHADAP GANGGUAN FUNGSIONAL AKIBAT NYERI DYSMENORRHEA PRIMER REMAJA PUTRI SMP NEGERI 9 DENPASAR - Ni Nyoman Satria Mas Agusti; I Made Niko Winaya; Luh Made Indah Sri Handari Adiputra (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT This study was conducted to analyze the addition of kinesiotaping in the abdominal intervention stretchingexercise better than the intervention of abdominal stretching exercise in primary dysmenorrhea. This study was anexperimental pre-test and post-test control group design, each group consisting of 11 people, with kinesiotaping onabdominal stretching exercise intervention in Group 1 and giving abdominal stretching exercise intervention in Group 2as a control group. Measurement of pain reduction rate was performed using Menstrual Distress Questionnaire (MDQ).After obtaining the data, the results showed that the addition of kinesiotaping to the abdominal intervention stretchingexercise had a decrease in pain of 42.55 ± 4.25 whereas only with abdominal exercise stretching exercise haddecreased pain of 23.45 ± 3.45 with p = 0.000 (p <0.05). Keywords: Primary dysmenorrhea, abdominal stretching exercise, kinesiotaping, Menstrual Distress Questionnaire(MDQ)